ANALISIS KETIMPANGAN PRODUKTIVITAS DAN DUALISME KETENAGAKERJAAN DI PROVINSI BENGKULU - Armelly Armelly; Novi Tri Putri; Retno Agustina Ekaputri; Lela Rospida (Convergence: The Journal of Economic Development, 2020)
The purpose of this study is to analyze labor productivity inequality and labor dualism in Bengkulu Province. The method used is descriptive analysis, equipped with class typology and elasticity of employment. We are using employment data from BPS publications. The results show that by dividing business fields into 17 sectors in 2018 and 2019, labor productivity inequality is awfully unequal, which is indicated by a very high standard deviation rate. Meanwhile, labor dualism is led by informal workers by a percentage of over 60%. More workers with primary education are absorbed in the informal sector, whereas educated workers are mostly taken in the formal sector. The highest coefficient of labor absorption elasticity for legal workers occurred in 2016 (3.14) and for informal workers in 2015 (1.73).Keywords: labor dualism, labor productivity